Environmental concern to attitude towards green products: evidences from India - Kirmani, Mohd Danish; Khan, Mohammed Naved (Serbian Journal of Management, 2016)
The purpose of this paper is to explore the relationship of environmental concern of consumers with their attitude towards green products and also to identify the predictors of environmental concern. The data was generated from a researcher controlled sample of graduate and post-graduate students enrolled in educational institutions located in the national capital of India (New Delhi) and surrounding areas popularly known as National Capital Region (NCR). The data generated was analysed employing Structural Equation Modelling (SEM). The study findings indicate that environmental concern has a significant and positive influence on attitude towards green products. Collectivism and eco-literacy emerged as predictors of the environmental concern of consumers. The findings of this study are expected to enhance the understanding of marketers of the role played by variables such as religiosity, collectivism, eco-literacy, and environmental concern in formation of attitude of consumers towards green products.